Combinatorial Image Analysis 14th International Workshop, IWCIA 2011, Madrid, Spain, May 23-25, 2011. Proceedings - Aggarwal, Jake K.; Barneva, Reneta P.; Brimkov, Valentin E.; Koroutchev, Kostadin N.; Korutcheva, Elka R. (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2011)
This volume constitutes the refereed proceedings of the 14th International Workshop on Combinatorial Image Analysis, IWCIA 2011, held in Madrid, Spain, in May 2011. The 25 revised full papers and 13 poster papers presented together with 4 invited contributions were carefully reviewed and selected from 60 submissions. The papers are organized in topical sections such as combinatorial problems in the discrete plane and space related to image analysis; lattice polygons and polytopes; discrete/combinatorial geometry and topology and their use in image analysis; digital geometry of curves and surfaces; tilings and patterns; combinatorial pattern matching; image representation, segmentation, grouping, and reconstruction; methods for image compression; discrete tomography; applications of integer programming, linear programming, and computational geometry to problems of image analysis; parallel architectures and algorithms for image analysis; fuzzy and stochastic image analysis; grammars and models for image or scene analysis and recognition, cellular automata; mathematical morphology and its applications to image analysis; applications in medical imaging, biometrics, and others.